1999
DOI: 10.1111/j.1095-8649.1999.tb02052.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prey mobility, prey contrast, turbidity and spectral composition on the reaction distance of Gobiusculus flavescens to its planktonic prey

Abstract: The reaction distance of Gobiusculus flavescens to mobile and immobile copepod prey of different transparency was studied in water conditions with different turbidity levels or spectral composition. Both prey contrast (red or transparent Calanus spp.) and prey mobility caused reaction distance of G. flavescens to increase. The effect of prey mobility or prey transparency on reaction distance was independent of turbidity level. Longest reaction distances were measured for mobile and red prey at intermediate tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(80 citation statements)
references
References 38 publications
6
74
0
Order By: Relevance
“…Since measurements were taken at mid-depth of each depth stratum, it is possible that the bulk of mackerel larvae had encountered suboptimal light levels on the second day of the drift study. However, reactive distance of fish larvae to their potential prey is also positively correlated to prey size (Aksnes and Utne 1997;Utne 1997) and mobility (Utne-Palm 1999). Therefore one might expect a higher proportion of larger and more mobile prey in the larval stomachs on the second day of our study.…”
Section: Cannibalistic Feeding In Atlantic Mackerel Larvaementioning
confidence: 83%
“…Since measurements were taken at mid-depth of each depth stratum, it is possible that the bulk of mackerel larvae had encountered suboptimal light levels on the second day of the drift study. However, reactive distance of fish larvae to their potential prey is also positively correlated to prey size (Aksnes and Utne 1997;Utne 1997) and mobility (Utne-Palm 1999). Therefore one might expect a higher proportion of larger and more mobile prey in the larval stomachs on the second day of our study.…”
Section: Cannibalistic Feeding In Atlantic Mackerel Larvaementioning
confidence: 83%
“…2 m) and devoid of macrophytes (potential shelters). Certainly, the water turbidity was too low to prevent fish from efficiently feeding on chaoborids (Bristow et al 1996, Utne-Palm 1999. A typical dark and poorly oxygenated hypolimnion, which could be a potential refuge for chaoborid larvae, did not develop in the reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…2), thus causing an additional change in the apparent contrast. Increase in turbidity can lead to increase in the inherent contrast for transparent prey such as cladocerans and compensate the reduction in the visual field (Utne-Palm 1999;De Robertis et al 2003). At high turbidities, the negative effects of turbidity on the apparent contrast overshadow the positive effects on inherent contrast and result in a reduced feeding efficiency.…”
mentioning
confidence: 99%
“…However, the feeding efficiency of fish does not always decline constantly with increasing turbidity. Some studies have shown that moderate turbidity values (up to 20-30 NTU) may enhance the feeding success of planktivores foraging on transparent prey by providing contrast between the background and the prey (Boehlert and Morgan 1985;Utne-Palm 1999;Horppila et al 2004). Turbidities exceeding 30 NTU usually result in a reduced feeding efficiency compared with clear water (Vinyard and O'Brien 1976;Utne-Palm 1999).…”
mentioning
confidence: 99%